Mergers & acquisitions in the Caribbean financial sector - Khan, Glen A. ed. (Caribbean Centre for Monetary Studies St. AugustineTT, 1997)
Presents an overview of the issues in mergers. Looks at bank consolidation; financial sector mergers and acquisitions; and, mergers between banks and insurance companies. Focuses on human resource issues in mergers and acquisitions as well as in mergers and acquisitions in the Caribbean.